Impact of Credit Risk, Distribution of Interest Rate, and Liquidity on Bank Profitability - Sari, Sinta Purnama (Institut Agama Islam Negeri Kendari, 2021)
Developing Islamic finance in Indonesia is needed to strengthen a sustainable economic structure. This issue is based on the promising potential of Islamic economic and financial development. This study examines the impact of credit risk, the spread of interest rates, and liquidity on bank profitability. The population in this study is Islamic banking companies in Indonesia during the 2014-2018 period. The sample was chosen from the purposive sampling method and obtained a sample of 50 companies from several criteria. This research uses multiple linear regression analysis with the help of SPSS version 21. This research shows that credit risk and liquidity affect bank profitability. At the same time, the spread of interest rates does not affect banks' profitability.